Agriculture-related energy consumption, food policy, and CO2 emission reduction: New insights from Pakistan - Raza, Muhammad Yousaf; Zhongpan, Qiu; Pengju, Wang (Frontiers in Environmental Science, 2023)
Fossil fuel energy consumption in the agriculture sector of Pakistan has created serious climate change issues, adding extremely to carbon dioxide emissions (CO2es), economic growth and food production. The current research has investigated the most carbon-emitting agriculture factors based on human activities, such as transportation, land, multiple crops, distribution, and consumption under various crops. Different machineries and frameworks applied in agricultural farming can mitigate the CO2es of the agriculture sector if the renewable energy technologies (RETs) and renewable energy sources are organized with proper agricultural loads. The major concerns of this paper show a road-map among (a) CO2es in the food supply chain and per capita CO2es, (b) food chain activities in the agriculture farming process, (c) the agriculture output units and energy consumption, and (d) decarbonization of traditional agriculture and sustainable development in the agriculture sector. The analysis shows that the RETs and mitigation frameworks can lessen the CO2es of farming depending on the type of farm and energy utilization. Finally, the present research highlights possibilities and opportunities for gaining CO2es in crop production linked with Pakistan’s goods management practices. Further policies are provided below.